IMPROVING THE QUALITY OF ELEMENTARY SCHOOL THROUGH HEADMASTER PRINCIPAL MENTORING PROGRAM: IMPROVING THE QUALITY OF ELEMENTARY SCHOOL THROUGH HEADMASTER PRINCIPAL MENTORING PROGRAM - Yosa Novia Dewi; Zefriyenni Zefriyenni; Khidayatul Munawwaroh; Efa Silfia; Sri Dewi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
As an independent country, Indonesia has aspired to educate the nation through education. However, now, education in Indonesia has many problems. The quality of school in Indonesia are still low, especially in marginal schools. It is located in outlying place, inland, or border. Dompet Dhuafa as one of the NGOs managing ZISWAF funds (Zakah, Infak, Sedekah, Waqaf) which is aimed to improve the welfare of the community through Makmal Pendidikan has made various efforts in advancing the education in Indonesia, especially in education for the poor (marginal). This research was conducted in 2019 up to 2020 in 2 marginal schools (Elementary School and Islamic Elementary School) located in Indonesia. This reseach is a quasi-experimental longitudinal study, through the MPC4SP Tools intervention. This tools is used to assess the schools that will be the target of mentoring assistance which consists of a score of 0 - 1000 points (level 1 to 5). The result of the school assessment is used as the basic data for the establishment and improvement of school performance through mentoring process for headmaster and teachers. MPC4SP are focused on 6 criteria: Leadership of Learning, Effectiveness of Learning, Literacy and Mathematics, Educational Leadership, Character building Learning Environment. The results showed that the increasing of school performance score, that is as much as 100 points in Elementary School and 220 points in Islamic Elementary School. It means that there is an increasing in the level of school quality from level 1 to level 2 in elementary school and level 3 to level 4 in Islamic elementary school after program intervention..